Optimization of EM4 Probiotic Supplementation in Feed to Improve the Health and Growth of Sangkuriang Catfish (Clarias Gariepinus Var.Sangkuriang) In an Intensive Cultivation System - Dwi Agung Saputra; Elfa Verda Puspita; Kalpri Sangra; Nadisa Theresia Putri (Jurnal Ilmiah Global Education, 2025)
Catfish farming is currently a promising business to pursue. The high market demand for fish provides opportunities for entrepreneurship in the aquaculture sector. The stable fish market makes catfish cultivation particularly attractive. Catfish are easy to grow, which is one of the supporting factors for the progress of catfish farming. In addition, their resistance to weather changes supports rapid development and allows farmers to choose catfish cultivation as the right business opportunity. However, there are still obstacles in catfish rearing, including diseases caused by bacteria, water quality issues, and feed quality problems. Therefore, alternative solutions are needed to overcome these challenges. One such solution is the use of probiotics, as they can optimize fish growth. A common example of probiotics used in aquaculture is EM4. This study aims to determine the best dosage of probiotics to enhance catfish growth and to examine the effect of probiotics on the growth performance of sangkuriang catfish (Clarias gariepinus). The research was conducted using an experimental method with four treatments: control (4 ml/kg), P1 (6 ml/kg), P2 (8 ml/kg), and P3 (10 ml/kg).